2016
DOI: 10.1111/papq.12170
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feeling of Presence

Abstract: Everyday visual experience constantly confronts us with things we can interact with in the real world. We literally feel the outside presence of physical objects in our environment via visual perceptual experience. The visual feeling of presence is a crucial feature of vision that is largely unexplored in the philosophy of perception, and poorly debated in vision neuroscience. The aim of this article is to investigate the feeling of presence. I suggest that visual feeling of presence depends on the visual repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 77 publications
2
40
0
Order By: Relevance
“…In this respect, as recent philosophical analysis of these experiments confirms, the visual feeling of presence of an object depends on the visual representation of a very particular spatial relation with it: the visual representation of egocentric absolute depth , which allows us to visually represent an object as vividly present (in our action space) and as offering possibility of interaction (Ferretti , , , )—that is, it allows us to reach the experience of stereopsis (Vishwanath ; Ferretti , , , ) as it concerns the fact that the “observer has knowledge of the depth relations scaled in some meaningful way to the actions of the observer” (Vishwanath , 222; see also 206–222).…”
Section: During Trompe L'oeil Perception the Surface Is Not Perceivementioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, as recent philosophical analysis of these experiments confirms, the visual feeling of presence of an object depends on the visual representation of a very particular spatial relation with it: the visual representation of egocentric absolute depth , which allows us to visually represent an object as vividly present (in our action space) and as offering possibility of interaction (Ferretti , , , )—that is, it allows us to reach the experience of stereopsis (Vishwanath ; Ferretti , , , ) as it concerns the fact that the “observer has knowledge of the depth relations scaled in some meaningful way to the actions of the observer” (Vishwanath , 222; see also 206–222).…”
Section: During Trompe L'oeil Perception the Surface Is Not Perceivementioning
confidence: 99%
“…As a result, we have the visual experience of a real object, of the kind we are usually acquainted with in ordinary perception of real objects , in which, indeed, we are in front of just one object we visually track and we have visual experience of. So, what makes trompe l'oeil perception and ordinary perception of real objects so similar concerning the visual feeling of presence is that, in both these perceptual situations, we do not perceive any surface, either consciously or unconsciously (see Ferretti ; Vishwanath ) and our visual experience presents us with what seems to be a present object we can interact with. However, in ordinary perception of real objects , the real object is, indeed, not embedded in any surface, while in trompe l'oeil perception the depicted object is embedded in a surface that, being not visible, cannot be tracked by our visual system.…”
Section: During Trompe L'oeil Perception the Surface Is Not Perceivementioning
confidence: 99%
See 1 more Smart Citation
“…However, much of the philosophical reflection that endorses the perceptual fusion of these two aspects investigates picture perception by analyzing the way in which different portions of our visual system are respectively attuned to the depicted object and to the surface (Nanay 2011: 464, 2015, 2017: sect. 2; Lopes 2005; Hopkins 2012; Ferretti 2016a, 2016c, 2017a). This is because ‘any account of seeing-in must be able to tell how this experience represents the picture's surface and how it represents the depicted object’ (Nanay 2010b: 199, cf.…”
Section: Pictures Surfaces and Depicted Objectsmentioning
confidence: 99%
“…Empirically informed philosophical accounts of picture perception that recognize and use the evidence reported by neuroscience about the several resemblances of face-to-face and picture perception (Nanay 2011, 2015; Ferretti 2016a, 2016c, 2017a) suggested that, despite such important resemblances, face-to-face and picture perception are different.…”
Section: Introductionmentioning
confidence: 99%